Rancang Bangun Sistem Penjualan dan Stok Opname Pada Toko Heri - Muhammad Sabiilul Hikam Azzuhrie; Farizi Ilham; Artha Mauludani; Reiksa Azra Octavian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The rapid development of information technology has encouraged various business sectors, including retail businesses, to utilize information systems in supporting their operational activities. Retail stores have main activities such as sales transactions and inventory management which are carried out routinely every day. However, in practice, many retail stores still record transactions and manage inventory manually, which often leads to various problems such as recording errors, delays in data updates, and difficulties in stock-taking processes and report generation. The purpose of this study is to design a sales and stock opname system that can help improve efficiency and accuracy in managing sales data and inventory in retail stores. The research methods used include observation, interviews, and literature study to obtain the information needed in the system analysis and design process. The result of this study is a design of an information system capable of automatically recording sales transactions, managing inventory data in an integrated manner, and providing stock opname features to facilitate the stock-checking process. In addition, the system is able to generate sales reports and inventory reports quickly and accurately. With this system, it is expected to assist store owners in improving operational effectiveness and minimizing errors in data management.